Factors influencing workplace social capital among registered nurses in China. (27th February 2021) - Xu, J.‐M.; Kunaviktikul, W.; Akkadechanunt, T.; Nantsupawat, A.; Turale, S.
Abstract : Aim: To examine the modifiable predictors and the level of workplace social capital, transformational leadership, emotional intelligence and organizational justice among registered nurses in Chinese hospitals. Background: Workplace social capital is a relational network developed among nurses and other healthcare professionals that provides social support, and gives value to their working lives. Internationally, cultivating high levels of social capital is critical as it can help improve nurse satisfaction and care, and address nurse turnover. However, knowledge of factors influencing nurses' workplace social capital is limited in China. Methods: In this cross‐sectional, descriptive predictive study, 344 registered nurses were randomly selected from three urban Chinese hospitals in Zhejiang province. Five standard instruments were applied to collect data. Descriptive statistics were used to present the level of the variables and stepwise multiple regression was performed to identify the predictors of nurses' workplace social capital. Results: Among eight potential factors, transformational leadership and emotional intelligence positively predicted workplace social capital. Nurses perceived the overall level of workplace social capital, emotional intelligence and unit managers' transformational leadership as high, and the overall level of organizational justice as moderate. Discussion: Enhancing unit managers' transformational leadership and nurses' emotional intelligence was found to positively influence the development of workplace social capital. Although it is not a predictor of workplace social capital, nurses' organizational justice should be improved due to its importance and current unsatisfactory level. Conclusion and implications for nursing and health policy: Nursing and health policymakers need to consider the enhancement of transformational leadership and emotional intelligence when implementing policies to improve nurses' workplace social capital, nursing retention and job satisfaction.